Inequalities in dental attendance throughout the life-course - Listl, Stefan (Journal of dental research, 2012)
The purpose of this study was to identify socio-economic inequalities in regular dental attendance throughout the life-course. The analyses relied on data from SHARE (waves 1 to 3 of the Survey of Health, Ageing, and Retirement in Europe), which includes retrospective information on life-course dental attendance of 26,525 persons currently aged 50 years or greater from 13 European countries (Austria, Poland, Spain, Italy, the Netherlands, Belgium, Greece, the Czech Republic, France, Denmark, Switzerland, Germany, and Sweden). Inequalities in dental attendance were assessed by means of Concentration Indices. Socio-economic disparities in regular dental attendance were identified as early as childhood. Moreover, higher educational attainment resulted in increased probabilities of regular dental attendance throughout subsequent life-years in all nations. In most countries, inequality levels remained relatively inelastic throughout the life-course. These findings suggest that a considerable proportion of inequalities in dental care use is already established at childhood and persists throughout the life-course.